Recognizing trade‐offs in multi‐objective land management. Issue 4 (2nd December 2011) - Bradford, John B; D'Amato, Anthony W
Abstract : As natural resource management and conservation goals expand and evolve, practitioners and policy makers are increasingly seeking options that optimize benefits among multiple, often contradictory objectives. Here, we describe a simple approach for quantifying the consequences of alternative management options in terms of benefits and trade‐offs among multiple objectives. We examine two long‐term forest management experiments that span several decades of stand (forest tree community) development and identify substantial trade‐offs among carbon cycling and ecological complexity objectives. In addition to providing improved understanding of the long‐term consequences of various management options, the results of these experiments show that positive benefits resulting from some management options are often associated with large trade‐offs among individual objectives. The approach to understanding benefits and trade‐offs presented here provides a simple yet flexible framework for quantitatively assessing the consequences of different management options.